Cation–π interaction of thallium (I) with [7]helicene: an experimental and theoretical study. (3rd June 2022) - Vaňura, Petr; Sýkora, David; Böhm, Stanislav; Uhlíková, Tereza
Abstract : Electrospray ionisation mass spectrometry was used to investigate the cation–π interaction of Tl + with [7]helicene. Further, applying quantum mechanical calculations in the frame of the density functional theory, applying B3LYP functional with Def2TZVP basis set, the most probable structure of the [7]helicene–Tl + complex was derived. In the resulting complex, the 'central' cation Tl + is bounded between two terminal benzene rings of the parent [7]helicene ligand via cation–π interaction. In such conformation, the [7]helicene creates a tweezer for Tl + ion. The interaction energy, E (int), of this cation–π complex was calculated to be –160 kJ/mol, which is consistent with the formation of the considered cationic complex species. Other structures were also found and generally lie energetically about 19–24 kJ/mol above the tweezer complex. HIGHLIGHTS Cation Tl + –[7]helicene complex has been observed using the ESI-MS method The structure of the resulting complex has been determined by applying quantum chemical DFT calculations Helicene functions as a chiral molecular tweezer for Tl + . GRAPHICAL ABSTRACT: UF0001